Liraglutide ameliorated peripheral neuropathy in diabetic rats: Involvement of oxidative stress, inflammation and extracellular matrix remodeling. Issue 2 (27th June 2018) - Moustafa, Passant E.; Abdelkader, Noha F.; El Awdan, Sally A.; El‐Shabrawy, Osama A.; Zaki, Hala F.
Abstract: Diabetic peripheral neuropathy is one of the most common microvascular complications that occurs with both type 1 and type 2 diabetes mellitus. It has a significant negative impact on patients' quality of life; as it starts with loss of limbs' sensation and may lead to lower limb amputation. This study aimed at investigating the effect of liraglutide on peripheral neuropathy in diabetic rats. Experimental diabetes was induced by single intraperitoneal injections of nicotinamide (50 mg/kg) and streptozotocin (52.5 mg/kg). Rats were allocated into five groups. Two groups were given saline or liraglutide (0.8 mg/kg, s.c.). Three diabetic groups were either untreated or treated with liraglutide (0.8 mg/kg, s.c.) or pregabalin (10 mg/kg, i.p.). After 2 weeks of treatment, behavioral, biochemical, histopathological, and immunohistochemical investigations were performed. Treatment with liraglutide‐restored animals' body weight, normalized blood glucose, decreased glycated hemoglobin, and increased insulin levels. In parallel, it normalized motor coordination and the latency withdrawal time of both tail flick and hind paw cold allodynia tests and reversed histopathological alterations. Treatment with liraglutide also normalized malondialdehyde, matrix metalloproteinase‐2 and ‐9 contents in sciatic nerve. Likewise, it decreased sciatic nerve nitric oxide and interleukin‐6 contents, DNA fragmentation and expression of cyclooxygenase‐2. Meanwhile, it increased superoxide dismutase and interleukin‐10 contents in sciatic nerve. These findings indicate the neuroprotective effect of liraglutide against diabetic peripheral neuropathy probably via modulating oxidative stress, inflammation, and extracellular matrix remodeling. Abstract : This study aimed to explore the possible protective effect of liraglutide on peripheral neuropathy in diabetic rats. Treatment with liraglutide restored animals' body weight, normalized blood glucose, decreased glycated hemoglobin and increased insulin levels. In parallel, it normalized motor coordination and the latency withdrawal time of both tail flick and hind paw cold allodynia tests and reversed histopathological alterations. Treatment with liraglutide also normalized malondialdehyde, matrix metalloproteinase‐2 and ‐9 contents in sciatic nerve. Likewise, it decreased sciatic nerve nitric oxide and interleukin‐6 contents, DNA fragmentation and expression of cyclooxygenase‐2. Meanwhile, it increased superoxide dismutase and interleukin‐10 contents in sciatic nerve.